Proceedings of the ACM Conference on Health, Inference, and Learning 2020
DOI: 10.1145/3368555.3384454
|View full text |Cite
|
Sign up to set email alerts
|

Variational learning of individual survival distributions

Abstract: The abundance of modern health data provides many opportunities for the use of machine learning techniques to build better statistical models to improve clinical decision making. Predicting time-toevent distributions, also known as survival analysis, plays a key role in many clinical applications. We introduce a variational timeto-event prediction model, named Variational Survival Inference (VSI), which builds upon recent advances in distribution learning techniques and deep neural networks. VSI addresses the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The study showed that a high FLC was significantly predictive of worse overall survival. Survivability predictions on this data set tend to give a C-index between 75% and 80% [11].…”
Section: Datasets Descriptionmentioning
confidence: 84%
See 1 more Smart Citation
“…The study showed that a high FLC was significantly predictive of worse overall survival. Survivability predictions on this data set tend to give a C-index between 75% and 80% [11].…”
Section: Datasets Descriptionmentioning
confidence: 84%
“…Variational inference is still an underexplored area in Survival Analysis. In a recent work, Xiu et al introduced the Variational Survival Inference (VSI) model [11], which uses variational inference to approximate p(t|x). The VSI model uses two encoders p(z|x) and q(z|x, t) and pushes these two distributions to be similar, using Kullback-Leibler divergence, to allow the model to better account for interactions between covariates and event times.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike standard observational studies with well-defined and observable outcomes, time-to-event measures fall into the range of survival analyses, which focus on the length of time until the occurrence of a well-defined outcome [23,33]. A characteristic feature in the study of time-to-event distributions is the presence of censored instances: events that do not occur during the follow-up period of a subject.…”
Section: Time To Next Engagementmentioning
confidence: 99%
“…More recent papers have explored the use of Discrete time models (Lee et al, 2018), recurrent neural architectures (Lee et al, 2019a) as well as fully parametric methods (Nagpal et al, 2020) for modelling survival outcomes in the presence of censoring. More involved techniques have involved the use of ensembles with black box optimization, auto encoding variational bayes (Chapfuwa et al, 2020;Xiu et al, 2020), as well as adversarial methods (Chapfuwa et al, 2018) to estimate survival outcomes.…”
Section: Related Workmentioning
confidence: 99%